Husband Support Correlates with Maternal Anxiety Levels During Pregnancy in The Third Trimester - Siska Nurul Abidah; Fritria Dwi Anggraini; Fauziyatun Nisa'; Mierda Nuriyana; Rahimah Halwa (Universitas Nahdlatul Ulama Surabaya, 2021)
Husband support reduces psychosocial stress on pregnant mothers before delivery. However, many people do not comprehend how essential husband support is for psychology in pregnant women. This study investigates the correlation between husband support and maternal anxiety levels during pregnancy in the third trimester. It was a correlational analysis using a cross-sectional approach. The population was pregnant mothers in the third trimester from May to July 2020 at Jagir Public Health Center, Surabaya. Meanwhile, the samples were 40 pregnant mothers in the third trimester with consecutive sampling. In addition. the independent variable was husband support, and the dependent variable was maternal anxiety levels. The instrument to measure husband support was a Likert scale questionnaire, and to assess maternal anxiety levels was Hamilton Anxiety Rating Scale (HARS). The analysis utilized the Rank's Spearman test with a significant p<0.05. The results showed a correlation between husband support and maternal anxiety levels with p=0.000 (p<0.05). In conclusion, husband support significantly reduces maternal anxiety levels during pregnancy in the third trimester.